REPRESENTASI FEMINISME DALAM FILM SLEEP CALL KARYA FAJAR NUGROS - Nopita, Kiki; Priyadi, Antonius Totok; Wartiningsih, Agus (Universitas Tanjungpura, 2025)
This study aims to analyze the representation of feminism in the film Sleep Call directed by Fajar Nugros by identifying scenes that depict gender injustice based on its various manifestations, including marginalization, subordination, stereotypes, violence, and workload. Furthermore, the findings of this study are expected to be implemented in the development of teaching modules for the Merdeka Curriculum in Indonesian language learning for grade VIII SMP (junior high school). This research uses a descriptive method with a qualitative approach. The data for this study were taken from the film Sleep Call, directed by Fajar Nugros and released on September 7, 2023. Data collection was carried out using the documentation method, utilizing various documents such as written papers, photos, and electronic files. Data analysis was performed using content analysis techniques, which involve a thorough examination of the textual elements within the film. The results of the study show that the representation of feminism in Sleep Call is reflected in 13 scenes that illustrate various forms of gender injustice, consisting of 1 scene of marginalization, 1 scene of subordination, 2 scenes of stereotypes, 7 scenes of violence, and 2 scenes of workload. These findings highlight how Sleep Call represents gender injustice issues relevant to feminist studies and can serve as a reference for integrating social issues into the Indonesian language teaching module.